A pack for spring - Emerson, Emilia (Cozyverse series., 2026)
"Lucy Andersson-Spring's twenty-ninth birthday comes with a side helping of a quarter-life crisis. She loves her community, her sewing shop, and her secret social media account featuring Starlight Grove's cat mayor, but maybe she needs to be more ambitious, more self-sufficient. At least, that's what the alphas she dated last year kept saying . . . before they cheated on her. Lucy is determined this year will be a fresh start, but her quest to leave her romantic dreams behind keeps being thwarted. First, a disastrous camping trip leaves her stranded with Wilder, the reserved fire chief. Then, a grumpy businessman named King bursts into her shop with a desperate proposal. And then there's Leo, the cute florist who brings her bouquets, but never the dinner invitation she hopes for. Like Lucy, these guys are facing crossroads in their lives, but when their hesitancy in wooing the stunning omega leaves her feeling rejected all over again, they realize they can't live without her. Determined to win her over, they embark on a journey of self-discovery, complete with a meddlesome cat, mischievous bunny, and bizarrely specific horoscopes, to become a pack worthy of her."--Amazon.